Multilingual Input System for the Web - an Open Multimedia Approach of Keyboard and Handwriting Recognition for Chinese and Japanese - Ramsey, Marshall C. (IEEE, 1998)
Artificial Intelligence Lab, Department of MIS, University of Arizona === The basic building block of a multilingual information retrieval system is the input system. Chinese and Japanese characters pose great challenges for the conventional 101 -key alphabet-based keyboard, because they are radical-based and number in the thousands. This paper reviews the development of various approaches and then presents a framework and working demonstrations of Chinese and Japanese input methods implemented in Java, which allow open deployment over the web to any platform, The demo includes both popular keyboard input methods and neural network handwriting recognition using a mouse or pen. This framework is able to accommodate future extension to other input mediums and languages of interest.